Islamic Education Values in Ki Hajar Dewantara's Concept of Education - Sofiani, Ika Kurnia; Roinah, Roinah; Nurhalin, Nurhalin; Ruzaini, Ruzaini (Journal of Educational Sciences, 2025)
This research addresses prevalent issues in Indonesia's education system, particularly the decline in moral character among the younger generation. The study aims to determine whether Ki Hajar Dewantara's educational framework lacks religious principles, contributing to these challenges, or if the problem lies in the disparity between his concept and the Islamic education model that emphasizes moral development. The research employs a library research method, reviewing various sources such as journals, books, and other references to gather information. The findings reveal that Ki Hajar Dewantara's educational framework does include Islamic educational values. The study concludes that the moral crisis in Indonesian education is not due to a lack of religious values in the educational concept but rather due to educators' failure to effectively implement Ki Hajar Dewantara's educational principles while understanding true Islamic education. This suggests the need for improved application of his concepts in educational practices, theories, and future development.